The Belt and Road The Global Strategy of China High-Speed Railway - Xu, Fei (Springer Singapore, 2018)
Addressing the unprecedented international interest in China's high-speed railways, this book adopts a global perspective to examine the success of the system and probes into its going-global strategy in the context of the "Belt and Road" initiative, providing readers around the world a better understanding of infrastructure construction under the "Belt and Road" plan, as well as the global vision of communication and mutual exchange and prosperity among the countries along the Belt and Road route. The previous American President, Barack Obama, once told President Xi Jinping that there were two things about China that he particularly admired: the high-speed railway system, and the mathematics education. "The Belt and Road, and the Global Strategy of China's High-speed Rail" provides scholarly researchers and those generally interested in China's High-speed rail excellent insight into this impressive and rapid development. .